The Influence of Lost and Found Unit Employee Performance in Handling Baggage at PT Gapura Angkasa on Passenger Satisfaction at Yogyakarta International Airport - Setyawati, Nanda Putri; Hodi, Hodi (Journal of Engineering Science and Technology Management (JES-TM), 2025)
PT Gapura Angkasa Yogyakarta International Airport provides ground handling services, including baggage services. The Lost and Found Unit plays a crucial role in handling passenger complaints related to lost or damaged baggage. However, problems are still frequently encountered in handling these complaints, which impact passenger satisfaction. This is thought to be related to unprofessional employee performance, particularly in terms of friendliness, responsiveness, and communication skills. The lack of training and briefings also impacts the quality of service provided. This study aims to determine the effect of Lost and Found Unit employee performance on passenger satisfaction. The approach used was a quantitative survey method with 96 respondents. The analysis technique used was simple linear regression to determine the extent of employee performance's influence on passenger satisfaction. The results showed a significant effect between employee performance and passenger satisfaction, with a t-value of 9.739 and a significance level of 0.000. The beta coefficient of 0.709 indicates a strong and positive relationship, while the R² value of 0.502 indicates that 50.2% of the variation in passenger satisfaction is influenced by employee performance. These findings emphasize the importance of improving employee professionalism, skills, and friendliness in efforts to improve passenger satisfaction with baggage handling services at the airport.